Analisis SWOT Perkembangan Dana Haji di Indonesia : Studi Pendekatan NVivo dan Literatur Review - Rohmadi; Doni Yusuf Bagaskara; Indah Yuliana (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2024)
This study aims to determine the SWOT analysis of the potential for Hajj Fund Development in Indonesia using the NVivo approach. This research uses qualitative methodology with Nvivo approach and literature review.